MODERN MILITARY GEOGRAPHY - Bezuidenhout, Jacques (Scientia Militaria - South African Journal of Military Studies, 2012)
Modern Military Geography is a new text that explores the relationship between geography and military conflict. As such, it covers many different scenarios and operational theatres and brings perspective to the link between local topography, hydrographical settings, climate, coastal conditions and military operations. The text goes further by examining the influence of secondary factors, which include, biological, health and environmental issues on military operations. The unique interaction between physical conditions and the geopolitical realities of different geographical settings are well illustrated. This book is therefore an excellent addition to the fields of military geography and military history, as well as other related military disciplines.